2000
DOI: 10.1128/aac.44.3.511-521.2000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proinflammatory Cytokines on the Interplay between Roxithromycin, HMR 3647, or HMR 3004 and Human Polymorphonuclear Neutrophils

Abstract: Cytokines, the hallmarks of infectious and inflammatory diseases, modify phagocyte activities and thus may interfere with the immunomodulating properties of antibacterial agents. We have investigated whether various proinflammatory cytokines (interleukin 1 [IL-1], IL-6, IL-8, gamma interferon, tumor necrosis factor alpha [TNF-␣], and granulocyte-macrophage colony-stimulating factor [GM-CSF]) modify two macrolide properties, i.e., inhibition of oxidant production by polymorphonuclear neutrophils (PMN) and cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
6
23
0
1
Order By: Relevance
“…We have previously reported that PKC activation by PMA impairs roxithromycin uptake (22). Similar data are obtained with all erythromycin A derivatives (M. T. Labro, unpublished data).…”
Section: Accumulation Kinetics Of Hmr 3562 and Hmr 3787supporting
confidence: 75%
“…We have previously reported that PKC activation by PMA impairs roxithromycin uptake (22). Similar data are obtained with all erythromycin A derivatives (M. T. Labro, unpublished data).…”
Section: Accumulation Kinetics Of Hmr 3562 and Hmr 3787supporting
confidence: 75%
“…Other authors have observed that proinflammatory cytokines (TNF-␣ and IFN-␥) increase macrolide uptake by macrophages or monocytic cell lines and favor the intracellular bactericidal activity of these drugs (30,31,290). Results from our group show a small (about 20%) but significant decrease in the uptake of roxithromycin and ketolides in TNF-␣-and GM-CSF-primed PMNs (397). In addition, these two cytokines decreased the inhibitory effect of HMR 3647 only on oxidant production by PMNs (397).…”
Section: Benzylpyrimidines (Trimethoprim and Analogs)mentioning
confidence: 71%
“…Results from our group show a small (about 20%) but significant decrease in the uptake of roxithromycin and ketolides in TNF-␣-and GM-CSF-primed PMNs (397). In addition, these two cytokines decreased the inhibitory effect of HMR 3647 only on oxidant production by PMNs (397). The clinical relevance of the antioxidant properties of macrolides is difficult to establish.…”
Section: Benzylpyrimidines (Trimethoprim and Analogs)mentioning
confidence: 88%
“…Activity against intracellular pathogens is the hallmark of macrolides and ketolides, but cellular uptake is required for these drugs to exhibit their activities (13,14). Contrary to macrolides, for which an extended literature on cellular uptake is available, few data are available on the uptake of ketolides (2,3,20,(29)(30)(31). The uptake of the ketolides HMR 3004 (formerly RU 64004) (30) and HMR 3647 (telithromycin) (31) and the fluoroketolides HMR 3562 and HMR 3787 (2) have been analyzed previously.…”
mentioning
confidence: 99%
“…HMR 3004 was used as a comparator drug. In addition, because all erythromycin A derivatives impair oxidant production by phagocytes (1,29,31), we also explored the effect of ABT-773 on this phagocyte function.…”
mentioning
confidence: 99%